2021
DOI: 10.1007/s11738-021-03265-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity stress on seedling biomass, physiochemical properties, and grain yield in different breeding wheat genotypes

Abstract: The salinity tolerance of 17 breeding wheat genotypes along with three local varieties was evaluated under control and salinity stress (160 mM NaCl) conditions. At the seedling stage, shoot and root dry weights, relative water content (RWC), membrane stability index (MSI), relative chlorophyll content (SPAD index), root and shoot Na + (RN and SN), root and shoot K + (RK and SK), root and shoot K + /Na + ratios (RKN and SKN), root-to-shoot Na + translocation (RTSN), root-to-shoot K + translocation (RTSK), stoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
2
10
0
Order By: Relevance
“…The PCA was based on the different principal components and each principal component has its eigenvalue which makes a percentage contribution to it (Table 3). The principal component that showed eigenvalues higher than 1 are considered significant while others are nonsignificant (Ahmed et al, 2019;Pour-Aboughadareh et al, 2021). The PCA results in this study was also similar to the findings reported by wheat scientists (Pour-Aboughadareh et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…The PCA was based on the different principal components and each principal component has its eigenvalue which makes a percentage contribution to it (Table 3). The principal component that showed eigenvalues higher than 1 are considered significant while others are nonsignificant (Ahmed et al, 2019;Pour-Aboughadareh et al, 2021). The PCA results in this study was also similar to the findings reported by wheat scientists (Pour-Aboughadareh et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Salinity stress is another environmental challenge that dramatically limits wheat production worldwide [121]. It has been reported that more than 800 million hectares of the world's total land are affected by salinity [122].…”
Section: Salinitymentioning
confidence: 99%
“…The root and shoot Na + and K + concentrations were detected as proposed by Pour-Aboughadareh et al [ 6 ]. Briefly, 10 mg of each sample was digested with 10 mL nitric acid (0.5 N) and maintained at 85 °C for 2 h in a boiling water bath.…”
Section: Methodsmentioning
confidence: 99%
“…Anecdotal evidence reveals that salt stress gently becomes a main limiting factor for plant growth and development, as well as an increase in a considerable loss of the productivity of crops. It is estimated that more than 800 million hectares of the world’s cultivated lands are affected by salinity [ 6 , 7 ]. However, despite escalating calls for more food in recent years, climate changes have caused increasing soil salinization in the wide areas around the world [ 8 ].…”
Section: Introductionmentioning
confidence: 99%